Solidaritas Sosial dalam Cerita Anak Berbahasa Jawa pada Majalah Jaya baya - Devita Kristiani; Haris Supratno; Suyatno Suyatno (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to describe social solidarity in Javanese children's stories in Jaya Baya magazine. The purpose of this research was to describe 1) forms of social solidarity in Javanese children's stories in Jaya Baya magazine; 2) driving factors for social solidarity in Javanese children's stories in Jaya Baya magazine and 3) the value of social solidarity in Javanese children's stories in Jaya Baya magazine.This research uses a collection of 53 Javanese children's stories from several different authors. The entire research data is sourced from the 2017 Jaya Baya magazine in the rubric "crita taman putra". The research data is described using descriptive methods and includes qualitative descriptive research. The collection of children's stories was analyzed using Emile Durkheim's social fact theory study of aspects of social solidarity. This theory study was used to describe the research focus of a variety of children's reading based on children's literature Donna E. Norton. The results of this research describe children's social solidarity in Jaya Baya magazine through three aspects, namely the form of social solidarity, driving factors for social solidarity and the value of social solidarity. The form of solidarity in children's stories in Jaya Baya magazine is described by parents' speeches and actions of children in friendship, family, community and environmental relations. The driving factor for social solidarity is influenced by Javanese ethics which emphasizes respect and harmony. Children's stories in Jaya Baya magazine describe the role of value as a stronghold of the influence of social dynamics, through the value of mutual assistance, the value of mutual cooperation and the value of tolerance. This shows that the results of this research emphasize the existence of patterns of interaction and socialization in realizing social solidarity.